Minimum Chemical Requirements for Adhesin Activity of the Acid-Stable Part of Candida albicans Cell Wall Phosphomannoprotein Complex - Kanbe, Toshio (American Society for Microbiology, 1998)
This study was conducted to define adhesive characteristics of the acid-stable moiety of the Candida albicans phosphomannoprotein complex (PMPC) on adherence of this fungus to marginal zone macrophages of the mouse spleen. Complete digestion of the acid-stable moiety (Fr.IIS) of the C. albicans PMPC with an α-mannosidase or hydrolysis with 0.6 N sulfuric acid destroyed adhesin activity, as determined by the inability of the soluble digests to inhibit yeast cell adherence to the splenic marginal zone. Fr.IIS adhesin activity was decreased following digestion with an α-1,2-specific mannosidase. Oligomannosyls consisting of one to six mannose units, which were isolated from the acid-stable part of the PMPC, did not inhibit yeast cell binding and thus do not function alone as adhesin sites in the PMPC. To gain more insight into the minimum requirements for adhesin activity, PMPCs were isolated from a Saccharomyces cerevisiae wild-type strain and from mutant strains mnn1, mnn2, and mnn4; the PMPCs were designated scwt/Fr.II, scmn1/Fr.II, scmn2/Fr.II, and scmn4/Fr.II, respectively. S. cerevisiae scmn2/Fr.II lacks oligomannosyl side chain branches from the outer core mannan, and scmn2/Fr.II was the only PMPC without adhesin activity. S. cerevisiae scwt/Fr.II, scmn1/Fr.II, and scmn4/Fr.II showed adhesin activities less than that of C. albicans Fr.II. These three S. cerevisiae PMPCs are generally similar to Fr.IIS, except that the S. cerevisiae structure has fewer and shorter side chains. Immunofluorescence microscopy show that the acid-stable part of the PMPC is displayed homogeneously on the C. albicans yeast cell surface, which would be expected for a surface adhesin. Our results indicate that both the mannan core and the oligomannosyl side chains are responsible for the adhesin activity of the acid-stable part of the PMPC.